An empirical investigation into the relationships among knowledge sharing behaviour,organizational citizenship behaviour, job satisfaction and organizational commitment - Boon, J.A. (Johannes Anton) (University of Pretoria, 2013)
Thesis (DPhil)--University of Pretoria, 2010.